2021
DOI: 10.1186/s12916-021-02059-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the safety profile of COVID-19 vaccines: a rapid review

Abstract: Background The rapid process of research and development and lack of follow-up time post-vaccination aroused great public concern about the safety profile of COVID-19 vaccine candidates. To provide comprehensive overview of the safety profile of COVID-19 vaccines by using meta-analysis technique. Methods English-language articles and results posted on PubMed, Embase, Web of Science, PMC, official regulatory websites, and post-authorization safety s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
174
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(203 citation statements)
references
References 98 publications
25
174
1
3
Order By: Relevance
“…However, in the current study, the incidences of headache and myalgia had no differences between the high, moderate dose and low dose, or between the first and second vaccination doses. No significant correlation between the dose and adverse events occurrence was found, consistent with the previous literature about COVID-19 vaccines [ 43 , 46 ]. Different vaccines have varied doses.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the current study, the incidences of headache and myalgia had no differences between the high, moderate dose and low dose, or between the first and second vaccination doses. No significant correlation between the dose and adverse events occurrence was found, consistent with the previous literature about COVID-19 vaccines [ 43 , 46 ]. Different vaccines have varied doses.…”
Section: Discussionsupporting
confidence: 91%
“…27 This is also consistent with the findings of Wu et al (2021) recent review of 87 publications with safety data from clinical trials and post-authorization studies of 19 COVID-19 vaccines. 35 Gastrointestinal symptoms, particularly nausea, were reported in 23.% of those who received AstraZeneca vaccine with lower proportions observed with the administration of Pfizer vaccine in two cross sectional studies (15.94% and 13.0%) and one randomized trial with the administration of Sinopharm vaccine (1%). [27][28][29]33 This trend was also observed in our study, though with higher proportions observed for AstraZeneca and Sinopharm vaccines and lower proportions with Pfizer vaccine.…”
Section: Discussionmentioning
confidence: 97%
“…27 In general, consistent with our findings, rates of local and systemic reactions were significantly lower among inactivated vaccines including Sinopharm vaccine compared to Pfizer and AstraZeneca vaccines as observed in Wu et al (2021) review. 35 Notably, localized lymphadenopathy was reported in two cross-sectional studies that included healthcare workers who were given Pfizer vaccine. 29,33 However, lower proportions were observed in our study perhaps due to lower health literacy among Jordanian population that might be affecting the ability to recognize lymphadenopathy symptoms compared to that expected from health care workers in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…We prepared a survey questionnaire after a careful review of COVID-19 data and surveillance from the Centers for Disease Control and Prevention (CDC) [22]. An extensive literature review on the associated side-effects of COVID-19 vaccines [8][9][10] and group discussion was integrated to finalize the questionnaire. Ethical approval was obtained from the human ethical review committee of the State University of Bangladesh to conduct the study (approval number: 2021-03-25/SUB/H-ERC/0005).…”
Section: Methods 21 Design and Sample Selectionmentioning
confidence: 99%
“…"Short length of the vaccine development process", "insufficient evidence to prove the efficacy of the vaccines", "safety evaluation of vaccines in the development process", and "potential side-effects recorded" were some of the most prevalent causes behind this [9]. Furthermore, when a global mass vaccination campaign was rolled out, certain severe and uncommon adverse events following immunization (AEFI) were observed [10].…”
Section: Introductionmentioning
confidence: 99%